The Impact of Oleuropein on Cisplatin-Induced Toxicity in Cochlear Cells in Relation to the Expression of Deoxyribonucleic Acid Damage-Associated Genes - Yüksel Olgun; Zekiye Altun; Merve Tütüncü; Selen Kum Özşengezer; Safiye Aktaş; Enis Alpin Güneri (Journal of International Advanced Otology)
BACKGROUND: Different organs respond differently to cisplatin (CDDP)-induced toxicity. Oleuropein (OLE) is a natural phenolic antioxidant. The purpose of this study was to determine the potential protective effect of OLE against CDDP-induced ototoxicity by evaluating expression of genes associated with deoxyribonucleic acid (DNA) damage and repair in cochlear cells.